Genetics of spontaneous cervical and coronary artery dissections - Rada, Isabel; Calderón, Juan Francisco; Martínez, Gonzalo; Muñoz Venturelli, Paula (Frontiers in Global Women's Health, 2023)
Objectives: Spontaneous cervical (SCeAD) and coronary artery dissections (SCoAD) are major causes of neurocardiovascular morbidity in young adults. Although multiple aspects of their etiology are still unknown, most consensuses are focused on the presence of constitutional genetic aspects and environmental triggers. Since recent evidence of genetic contribution suggests overlap between these conditions, we aimed to describe current information on SCeAD and SCoAD genetics and potential shared pathological aspects. Methods: Narrative review considering publications in English and Spanish. The articles were evaluated by one team member in terms of inclusion criteria. After collecting, the articles were categorized based on scientific content. Results: Patients with SCeAD and SCoAD rarely present connective tissue disorders; other genetic loci are probably responsible for the increased susceptibility in some individuals. The common variant rs9349379 at PHACTR1 gene is associated with predisposition to pathologies of the arterial wall, likely mediated by variations in Endothelin-1 (ET-1) levels. The risk of arterial dissection may be increased for those who carry the rs9349379(A) allele, associated with lower expression levels of ET-1; however, the local effect of this vasomotor imbalance remains unclear. Sex differences seen in SCeAD and SCoAD support a role for sex hormones that could modulate risk, forcing vasodilator actions over vasoconstriction due to a ET-1 reduction. Conclusions: New evidence points to a common gene variation that can explain dissection in both the cervical and coronary vasculatures. To further confirm the risk conferred by the rs9349379 variant, genome wide association studies are warranted in larger and ethnically diverse populations.